Relationship Power Imbalance and Known Predictors of Intimate Partner Violence in Couples Planning to Get Married: A Baseline Analysis of the AMAR Cohort Study - Martín-Lanas, Raquel (Journal of interpersonal violence, 2021)
The increased interest on measuring violence in romantic relationships has led to the identification of some risk factors for intimate partner violence (IPV) in its different forms. Some of them are often present from the onset of the relationships. However, little attention has been paid to the engagement period. This might be, in part, due to the cognitive dissonance that hinders partners reporting intimate violence when they are planning their wedding. The purpose of our study is to test the association between the individual perception of relationship power imbalance (RPI)—a possible indirect measure of intimate violence—and known predictors of IPV. To test this hypothesis, a total of 254 premarital couples taking part in a dynamic prospective cohort study completed a questionnaire with questions about the perception of RPI and referred predictors of IPV. Results showed a positive correlation between the perception of RPI and known predictors of IPV. These findings suggest that RPI is a powerful indirect measure to detect situations that might imply a mild form of IPV and that could evolve into stronger presentations of violence later in marriage. Noticing the presence of RPI before marriage could encourage the prevention and development of personal and relational strategies to avoid the consolidation of violent dynamics within the marital relationship.